The Design of Incentive Mechanism for Policy-Oriented Guarantee Institutions’ Digital Transformation in China - Youqing Lv; Guojian Ma; Linlin Lv; Juan Ding (Discrete Dynamics in Nature and Society)
Currently, China is actively promoting the reform process of the digital economy, and the digital transformation of the credit financing guarantee sector is gradually emerging. As the core driving force for the progress of digital transformation, the optimal design of the incentive mechanism is undoubtedly essential. Based on the principal-agent relationship between local governments and policy-oriented guarantee institutions, this study constructs a basic incentive model (model I) and an incentive model introducing a regulatory signal (model II), empirically analyzes the digital transformation effort of guarantee institutions under the influence of different factors and discusses how local governments should design the optimal incentive mechanism. The results show that the digital transformation effort level of guarantee institutions in model II is higher than that in model I, while the incentive intensity of local governments in model II is lower than that in model I. Within the range of guarantee compensation rate less than a specific threshold, the risk perception degree has negative effects on the effort level and incentive intensity of DT. In addition, the regulatory intensity has a constant negative effect on the incentive intensity of the DT, while it has a negative effect on the effort level of the DT only if the guarantee capacity is below a specific threshold. The research results can provide practical guidance for local governments to effectively promote digital transformation activities and improve the competitiveness of credit financing guarantee.